The barrio school teacher an ethnography of teaching - Landagan, Oscar Ledesma 1948- (Education quarterly.)
This case study indicates the need to address the survival needs of the teachers assigned in the barrio. To raise teachers? enthusiasm for teaching, the bureaucracy has an obligation to provide instructional support services and monetary incentives. It may also also attract talented students to consider barrio teaching as a career.